Biopsychosocial evaluation of patients with multiple sclerosis using a short set of categories of the international classification of functioning, disability and health, and its relationship with working capacity - Valadkevičienė , D.; Žukauskaitė , I.; Jatužis , D. (Neurologijos seminarai, 2018)
Background. During the recent decade, the working capacity of patients with multiple sclerosis (MS) in many countries is determined by International Classification of Functioning, Disability and Health (ICF) based on biopsychosocial view. It not only identifies the condition of health of patients, but also suggests measures to improve their inclusion into society. However, in Lithuania, the ICF principles for determining the level of working capacity are applied in a fragmentary way, and more often the biological-physical parameters of a person’s health status are used. Thus, the establishment of relationship between ICF and working capacity level would create assumptions to legitimize the use of this classification that subsequently would contribute to the well-being of people with MS. The aim of this research is to carry out a comprehensive biopsychosocial assessment of Lithuanian MS patients and to determine how their level of working capacity is related to the results of various categories of ICF.Subjects and methods. The cross-sectional study involved 184 people with MS including 157 people who had applied to the Disability and Working Capacity Assessment Office under the Ministry of Social Security and Labour of the Republic of Lithuania (DWCAO) to determine their working capacity level and 27 people with MS who hadn’t yet applied to DWCAO. The subjects were interviewed using a brief ICF core set for MS; sociodemographic and disease data were also collected.Results. 66% of patients with MS reported that they had a complete difficulty of moving around by means other than walking (ICF category d455), 32% – remunerative employment (d850). 81% of patients with MS had no difficulties in higher-level cognitive functions (b164), 63% in carrying out daily routine (d230), 57% – in solving problems (d175). 7–10% of patients faced negative attitudes of their family members or health care specialists and they considered it as a difficulty. Those with working capacity level of 0–25% faced higher difficulties in almost all ICF categories, compared to people with higher working capacity. MS patients with working capacity level of 30–40% had more difficulties of seeing, urination, muscle power functions, walking and moving around by means other than walking than MS patients with working capacity level of 45–55%; they also faced more difficulties in moving around functions and had a different brain structure than those with working capacity level of 60–100%.Conclusions. The value of ICF categories for assessment of the working capacity level of people with MS is different. The higher the level of person’s working capacity, the less restrictions patients with MS indicate in assessing ICF categories.
Keywords: multiple sclerosis; working capacity; disability; International Classification of Functioning; Disability and Health